PENGARUH PEMBERIAN BERBAGAI KADAR GETAH BUAH PEPAYA (CARICA PAPAYA, L.) TERHADAP JUMLAH KUMULATIF KEMATIAN LARVA AEDES AEGYPTI - Widiastti, Rina; Ismiyati, Ismiyati; Aini, Resmi (Universitas Ahmad Dahlan, 2015)
AbstractBackground: Papaya is a kind of plats which has the medicinal effect. Papaya?s sap (latex) contains papain, cimopapain and lysozim as protein destructor enzyme. Satrija guess that these enzymes has an anthelmintical activity. The research aim was to know the influence of papaya?s sap (latex) as a larvacide in several kind of doses (concentration).Methods: This research was true experimental design with posttest only control group design. Papaya?s sap was made as powder, afterward it was used for the research to know influence of Papaya?s sap in several kinds of doses (consentration) related to larval cumulative mortality rate of Aedes aegypti. Larvicidal activity was calculated based on larval mortality after 24 hours of exposure that was taken notes for each treated group. Data processing used SPSS program version 11,0 with significance 95% that contains data normality test, varians homogeneity test, One Way Anova, and Scheffe Post Hoc Test to know difference in larval cumulative mortality rate.Results: The result from Anova test shown a significant result in cause larval cumulative mortality rate of Aedes aegypti (p-value < 0.05) in comparison with negative gontrol group. Treated group with Papaya?s sap 1% shown higest larvacidal activity.Conclusion: Papaya?s sap has larvacidal activity at the concentration of 0,16%; 0,3%; 0,5%; and 1%. At concentration of 1%, papaya?s sap shown higest larvacidal activity and shown a significant result. Keywords: papaya, larvacide, larvae of Aedes aegypti